2004
DOI: 10.1021/es035208+
|View full text |Cite
|
Sign up to set email alerts
|

Estimating Potential Environmental Loadings ofCryptosporidiumspp. andCampylobacterspp. from Livestock in the Grand River Watershed, Ontario, Canada

Abstract: Exposure to waterborne pathogens in recreational or drinking water is a serious public health concern. Thus, it is important to determine the sources of pathogens in a watershed and to quantify their environmental loadings. The natural variability of potentially pathogenic microorganisms in the environment from anthropogenic, natural, and livestock sources is large and has been difficult to quantify. A first step in characterizing the risk of nonpoint source contamination from pathogens of livestock origin is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 56 publications
(22 reference statements)
0
36
0
Order By: Relevance
“…Both gene targets were detected most frequently at the Canagagigue Creek sampling location. The Canagagigue Creek subwatershed is located in a region with the highest livestock density in the watershed (Dorner et al 2007) and where estimates for daily manure production were also highest (Dorner et al 2004). for Yersinia in water also noted a higher rate of isolation during colder months of the year (Meadows & Snudden 1982;Fukushima et al 1984).…”
Section: Confirmation Of Quantitative Pcr Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both gene targets were detected most frequently at the Canagagigue Creek sampling location. The Canagagigue Creek subwatershed is located in a region with the highest livestock density in the watershed (Dorner et al 2007) and where estimates for daily manure production were also highest (Dorner et al 2004). for Yersinia in water also noted a higher rate of isolation during colder months of the year (Meadows & Snudden 1982;Fukushima et al 1984).…”
Section: Confirmation Of Quantitative Pcr Resultsmentioning
confidence: 99%
“…It provides part of the drinking water supply for approximately 500,000 people, and is also used for recreational activities (Dorner et al 2004). This system is one of the most heavily impacted watersheds in Canada, receiving inputs from both agricultural and urban activities (Dorner et al 2004), and a number of enteric pathogens typically found in surface waters have been previously detected (Dorner et al 2007). This research provides information for an emerging waterborne pathogen that is not well characterized in water sources.…”
Section: Introductionmentioning
confidence: 99%
“…Microbial pathogen modeling basically incorporates specific information about microbial dynamics in conjunction with soil composition, hydrological dynamics, climatic conditions, vegetation, and land management (35). It has been clearly demonstrated that mathematical models for bacteria are not suitable for predicting the fate and transport of parasitic protozoa (17,28,35). In particular, fecal indicators fail to reflect water contamination by Cryptosporidium and Giardia parasites because of the ability of oocysts and cysts to interact and aggregate reversibly with other particles, in contrast to other microorganisms (35,49).…”
Section: Implications For Natural Resource Managementmentioning
confidence: 99%
“…In particular, fecal indicators fail to reflect water contamination by Cryptosporidium and Giardia parasites because of the ability of oocysts and cysts to interact and aggregate reversibly with other particles, in contrast to other microorganisms (35,49). Several specific models have been successfully used for estimating protozoan loads in watersheds in some particular contexts (17,28,35). To our knowledge, no such models exist for Toxoplasma oocysts on a large scale, mainly because there is too little information on their transport properties, survival, and prevalence in the environment (31,60,100).…”
Section: Implications For Natural Resource Managementmentioning
confidence: 99%
“…The Grand River (south western Ontario, Canada) has been thoroughly characterized, with studies ranging from nutrient uptake (BARLOW-BUSCH et al, 2006), species composition along seasonal and nutrient gradients (METCALFE-SMITH et al, 2000;ROTT et al, 1998;SREENIVASA and DUTHIE, 1973), nitrogen cycling (ROSAMOND et al, 2011), fish ecology (COOKE and BUNT, 1999) to health risks from livestock rearing (DORNER et al, 2004) and human activities (LISSEMORE et al, 2006). The Grand River receives agricultural and urban inputs from both point (sewage plants, tile drainage) and non-point sources (agriculture, chiefly from manure spreading).…”
Section: Introductionmentioning
confidence: 99%